2005
DOI: 10.1124/dmd.105.006742
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Enzyme(s) Involved in the Metabolism of Amiodarone in Liver and Intestine of Rat: The Contribution of Cytochrome P450 3a Isoforms

Abstract: ABSTRACT:In humans, cytochrome P450 3A (CYP3A4) is a major enzyme involved in the metabolism of amiodarone (AM) to its major metabolite, desethylamiodarone (DEA). In rat, a commonly used animal model, metabolism of AM has not been well studied. To determine whether DEA is formed by CYP3A isoenzymes in the rat, microsomal protein was harvested from liver and intestine of male Sprague-Dawley rats. The metabolism of AM in each tissue was assessed utilizing chemical and immunological inhibitors. Ketoconazole, a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 33 publications
(54 reference statements)
5
38
0
Order By: Relevance
“…The fraction of the dose of AM converted to DEA was recently estimated to be up to 64% in rat (8). Earlier reports have demonstrated the involvement of CYP3A4, 1A1, 2D6 and 2C8 in DEA formation in human whereas CYP3A1 and 1A1 were found to be involved in DEA formation in rats (9)(10)(11). Similar to the parent drug, DEA possesses antiarrhythmic activity of its own.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fraction of the dose of AM converted to DEA was recently estimated to be up to 64% in rat (8). Earlier reports have demonstrated the involvement of CYP3A4, 1A1, 2D6 and 2C8 in DEA formation in human whereas CYP3A1 and 1A1 were found to be involved in DEA formation in rats (9)(10)(11). Similar to the parent drug, DEA possesses antiarrhythmic activity of its own.…”
Section: Introductionmentioning
confidence: 99%
“…An HPLC method was used for analysis of AM and DEA (11,28). The assay had a validated lower limit of quantitation of 35 ng/ml for both AM and DEA based on 100 µL of rat plasma (28).…”
Section: Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Four selective P450 inhibitors [10 M pilocarpine to CYP2A1 (Kimonen et al, 1995;Lewis, 1998); 30 M diethyldithiocarbamate to CYP2E1 (Eagling et al, 1998); 5 M ketoconazole to CYP3A1/2 (Ghosal et al, 1996;Shayeganpour et al, 2006); and 100 M sulfaphenazole to CYP2C subfamily (Eagling et al, 1998)] and two carboxylesterase inhibitors (TOCP, a nonselective microsomal carboxylesterase inhibitor, and PMSF, a selective hydrolase A inhibitor) at various concentrations were used to study their effects on the microsomal metabolism of clivorine in female rats. The concentrations of individual P450 inhibitors utilized were chosen based on the published reports as indicated above, to achieve significant inhibitions of the corresponding isozymes in rat liver microsomes.…”
Section: Animals and Preparation Of Liver Microsomesmentioning
confidence: 99%
“…Rat CYP3A2 and human CYP3A4 are involved in the metabolism of erythromycin, nifedipine, lidocaine, testosterone, aflatoxin B1 and benzo[a]pyrene (28,30). Furthermore, CYP3A4 is highly expressed in the adult liver and small intestine (30), and metabolizes xenobiotics and carcinogens (32,33), as well as numerous endogenous compounds, such as bile acids, cholesterol, prostaglandins, fatty acids, retinoids, leukotrienes and biogenic amines (32,34). The induction of CYP3A2 by SDC may be attributed to the presence of taurine, as it was demonstrated that taurine enhanced the induction of CYP3A4 by rifampicin in HepG2 cells (35).…”
Section: Discussionmentioning
confidence: 99%